(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
The choice of the right ﬁ scal regime represents the main object of the energy policy concerning hydrocarbon exploration and production for the state government. For the operator and service companies it represents the terms and conditions for practical conducting of the process in whole. This paper analyse aspects of agreements used in the petroleum indus-try. Elements of agreement, regardless of regime, have been described together with their advantages and disadvantages. Due to the fact that the ﬁ scal regime has to be chosen to attract companies willing to invest in exploration and produc-tion, it represents a relevant part of the business strategy and also a base for the decision making process during start up. It has to minimize the risk for the both parties involved and maximize the state’s share during the exploitation phase. For the companies, it has to be attractive enough to balance risks during the exploration phase with proﬁ ts gained during the exploitation phase. The aim of this paper is to show the existing ﬁ scal systems in the petroleum industry and to analyze the process for concluding a contract regarding the exploration and production of hydrocarbons. An overview of diﬀ er-ent business practices in the oil and gas industry with a detailed breakdown of the contract terms between the parties involved have been described in the paper. The aim of this paper is to show the diﬀ erent possibilities of ﬁ nancial regimes which could help during the negotiation process for conducting hydrocarbon exploration and production for everyone involved.